2021
DOI: 10.3389/fped.2021.692256
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Pediatric Acute SARS-CoV-2 Infection and Multisystem Inflammatory Syndrome in Children (MIS-C): Is There a Difference?

Abstract: Objective: To evaluate the prevalence and factors associated with the risk of acute kidney injury (AKI) in pediatric patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and multisystem inflammatory syndrome in children (MIS-C).Study Design: We performed a retrospective chart review of 113 patients with SARS-CoV-2 infection with or without MIS-C admitted at Children's Hospital of Michigan (CHM) from March to August 2020. Patient demographic details, laboratory data, imaging stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…We do not agree with the notion that COVID-19 in pediatric patients usually takes a mild course (Krueger et al 2021). There are several reports about paediatric patients with severe COVID-19 or its complications (O'Loughlin et al 2021;Grewal et al 2021).…”
Section: Letter To the Editorcontrasting
confidence: 90%
“…We do not agree with the notion that COVID-19 in pediatric patients usually takes a mild course (Krueger et al 2021). There are several reports about paediatric patients with severe COVID-19 or its complications (O'Loughlin et al 2021;Grewal et al 2021).…”
Section: Letter To the Editorcontrasting
confidence: 90%
“…Additionally, among 277 MIS-C patients with renal involvement identified during our literature search, the most commonly reported manifestation was AKI ( Table 1 ). Compared to patients without AKI, it was more frequent among patients who had cardiac dysfunction, required inotropic support, and ICU admission ( 26 ). Accordingly, pathogenesis of AKI appears to be predominantly pre-renal ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients without AKI, it was more frequent among patients who had cardiac dysfunction, required inotropic support, and ICU admission ( 26 ). Accordingly, pathogenesis of AKI appears to be predominantly pre-renal ( 26 ). On the other hand, severity of kidney dysfunction in patients with AKI did not correlate with degree of cardiac dysfunction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors perhaps hastily concluded that hematuria is an early sign of MIS-C, especially in a patient with no apparent acute kidney injury (normal creatinine level). Nor is this the first published case of MIS-C-related hematuria at the time of the article's release ( 16 , 31 ). Therefore, the content of the article does not correspond with the title of the article.…”
Section: Discussionmentioning
confidence: 99%